Microfinance Against Poverty : The Nepalese Scenario - Sharma, Shalik Ram (NRB Economic Review, 2003)
Microfinance institutions, both formal and informal, provide financial services which help in creating self-employment and income opportunities among the poor. NRB has made a number of innovative attempts for developing microfinance framework in the country. The article attempts to analyze the extent of the access provided, and the generation of employment opportunities, by the formal and semi-formal microfinance institutions/programs in addition to identifying the problems faced in attaining financial sustainability by them. In view of the increasing need for microfinance services in terms of both the amount and coverage, NRB needs to enhance its capabilities to regulate, supervise and monitor large number of MFIs and also come up with innovative and suitable credit policies/regulations that would create an enabling environment for MFIs to grow and attain sound financial health. Some of the desired roles for HMG are demonstrating firm commitment towards poverty alleviation through action, stopping direct involvement in running and managing MFIs, stopping owning MFIs, and handing over presently owned shares of such institutions to the private sector through appropriate and transparent mechanism.